Mixed-type autoimmune hemolytic anaemia complicated by acute cerebral infarction: a case report - Wang, Lei; Li, Hui; Zhao, Hao; Wang, Zhonglin (Frontiers in Medicine, 2025)
BackgroundIn patients with autoimmune hemolytic anaemia (AIHA), numerous factors can influence disease severity, and thrombotic complications are associated with increased morbidity and mortality. Reports of autoimmune hemolytic anemia complicated by acute cerebral infarction are relatively rare.Case presentationWe report a case of an 82-year-old female patient with hypertension who developed mixed-type AIHA complicated by acute cerebral infarction following intravenous infusion of ceftriaxone after erysipelas in which the patient’s previous hemoglobin (Hb) level was maintained at approximately 108 g/L. After developing erysipelas and treatment with ceftriaxone, the patient experienced a continuous decline in Hb, hematocrit (HT), and red blood cell (RBC) counts. Direct antiglobulin test (DAT) was positive for IgG and C3d, and both the reticulocyte count and proportion were elevated. The treatment regimen included methylprednisolone, enoxaparin for anticoagulation, and clopidogrel for antiplatelet aggregation. Following targeted treatment, the patient’s condition improved.ConclusionClinicians should be aware of the potential contributing factors in patients with mixed-type AIHA who develop neurological deficits due to severe anemia. This case report aims to emphasize the laboratory aspects of mixed-type AIHA and the necessity for clinicians to recognize the potentially fatal consequences of acute thromboembolism in mixed-type AIHA.